Rancang Bangun Sistem Konsentrator Cahaya Matahari Dengan Lensa Fresnel Untuk Meningkatkan Intensitas Cahaya Matahari Pada Panel Solar Cell - Dwi Permata Sari; Parlin Siagian; Dino Erivianto (CV. Hawari, 2025)
Solar energy is one of the potential and environmentally friendly renewable energy sources. However, the efficiency of sunlight absorption by solar panels is often affected by the intensity of light received. This study aims to design and build a solar light concentrator system using a Fresnel lens to increase the intensity of light received by the solar panel. The issues addressed in this research include how to design a device with a Fresnel lens that can focus sunlight and how the use of this lens affects the electrical power generated by the solar panel. The research method includes the mechanical design of the concentrator system, installation of the Fresnel lens, and testing of light intensity and the output power of the solar panel before and after the lens application. This study is limited to the analysis of increased intensity and electrical power, without considering cost aspects or economic efficiency.